2008
DOI: 10.1117/1.2952076
|View full text |Cite
|
Sign up to set email alerts
|

One-year study on the variation of carotenoid antioxidant substances in living human skin: influence of dietary supplementation and stress factors

Abstract: Variation in the level of the carotenoid antioxidant substances beta-carotene and lycopene in the human skin of ten healthy volunteers was measured with resonance Raman spectroscopy in an in vivo experiment over the course of 12 months. Information on the lifestyle of the volunteers concerning dietary supplementation and stress factors was obtained daily by the completion of questionnaires. The results showed individual variations in the levels of carotenoid antioxidant substances in the skin of the volunteers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
142
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(148 citation statements)
references
References 27 publications
5
142
1
Order By: Relevance
“…Availability represents an important barrier for the intake of fruits and vegetables 207 in some countries (6), and harvests might determine choice in intake of fruits and 208 vegetables in others (8,27). Health patterns such as normal blood pressure (28), absence 209 of cardiovascular disease (9), and normal lipid levels (12,13) are likely to be the result 210 of lifestyle, genes, and environmental characteristics, but their relation to seasonal 211 variation has not been clearly linked.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Availability represents an important barrier for the intake of fruits and vegetables 207 in some countries (6), and harvests might determine choice in intake of fruits and 208 vegetables in others (8,27). Health patterns such as normal blood pressure (28), absence 209 of cardiovascular disease (9), and normal lipid levels (12,13) are likely to be the result 210 of lifestyle, genes, and environmental characteristics, but their relation to seasonal 211 variation has not been clearly linked.…”
Section: Discussionmentioning
confidence: 99%
“…There was a 32 linear and significant increase of vegetable intake for women, whereas the variation was 33 non-linear and of lesser magnitude for men (4). 34 Food intake variation throughout the seasons, sex, and age might be relevant if the 35 variation increases the likelihood of diseases (8,9), but it is even more relevant if it 36 introduces measurement bias (10,11). Since they represent a source of variation and a 37 potential bias, the seasons can influence patterns of health.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] The nonenzymatic antioxidant defense system consists of low-molecular-weight components such as chromophores (carotenoids, melanins, urocanic acids, porphyrins, bilurubins, flavins, and pterins) and vitamins (A, B, C, D, and E), whereas the enzymatic antioxidant defense system is composed of various types of antioxidant enzymes (superoxide dismutase, peroxidase, catalase, and glutathione reductase). [9][10][11][12][13] When the number of ROS exceeds a critical threshold due to the saturation in capacity of the antioxidant defense system, ROS cause oxidative damage to the cells, leading to skin damage in forms such as premature skin aging and even skin cancer, 14,15 Under certain circumstances, the endogenous chromophores such as porphyrins (uroporphyrin, coproporphyrin, and protoporphyrin), bilurubins, melanins (eumelanin and pheomelanin), flavins (riboflavin, flavin mononucleotide), pterins (6-carboxypterin, formylpterin, neopterin, and biopterin), and urocanic acid (trans-urocanic acid) act as photosensitizers. 16 A photosensitization reaction is initiated by the absorption of visible light and UVA radiation by a photosensitizer, forming the singlet excited state.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that dietary supplementation of antioxidants may provide efficient protection against extrinsic skin ageing. Environmental inducers of ROS, such as UVR exposure, can lead to a reduction in antioxidants and an increase in levels of oxidative stress [46]. There is emerging evidence that antioxidant supplementation may be able to protect human skin against UVR damage.…”
Section: Dietmentioning
confidence: 99%
“…Carotenoid substances, found in fruit and vegetables, as well as vitamins A, C and E, are said to be the most protective and correlate negatively with levels of oxidative stress [45]. A study examining the influence of lifestyle factors on the level of carotenoid antioxidants beta-carotene and lycopene found that antioxidant levels in the skin significantly increased with dietary consumption of carotenoid-rich food [46]. The results indicated that dietary supplementation of antioxidants may provide efficient protection against extrinsic skin ageing.…”
Section: Dietmentioning
confidence: 99%